Preliminary Study On The Fabrication And Characterization Of Lightweight Porcelain Tiles Via Tri-Layer Pressing Method - Juhari_, Muhammad Syahir (Universiti Sains Malaysia, 2017)
The aim of this study is to fabricate and characterize lightweight porcelain tiles by tri-layer pressing method. Lightweight porcelain tiles consists of three different layer whereby upper and bottom layer contain commercial porcelain powder and middle layer consists of mixture of commercial porcelain powder and calcium carbonate (CaCO3). Parameters studied in this work were weight ratio commercial porcelain powder/calcium carbonate in the middle layer (0% CaCO3 + 100% porcelain powder, 5% CaCO3/95% porcelain powder, 10% CaCO3/90% porcelain powder and 15% CaCO3/85% porcelain powder) with two firing temperature (1050 ⁰C and 1150 ⁰C). The mixture of the commercial porcelain powders and CaCO3 are weight according to the ratio and dry mixed in HDPE bottle, uniaxial pressing (tiles shape; length: 10cm, width: 5cm, height: 0.5cm) followed by drying for 24 hours before firing. Fired samples were characterized by appearance observation, volumetric shrinkage, bulk density, water absorption, modulus of rupture (MOR), coefficient of thermal expansion (CTE) and X-ray Diffraction (XRD) analysis for phase identification. Samples with 90 %Porcelain/10 %CaCO3 (T3, T7) fired at 1150 ⁰C show lowest density (2.13 g/cm3) and highest water absorption (5.56%). At 1150 ⁰C, fired tiles are able to reduce down the density to around 1.38% to 2.13% of the density of control sample (2.18 g/cm3). However, samples with 15% CaCO3/85% porcelain powder (T4, T8) faced delamination problem. CTE result prove that delamination are not occur due to different in thermal expansion between middle layer with top and bottom layer.